Prevention of glucocorticoid morbidity in giant cell arteritis. (23rd February 2018) - Buttgereit, Frank; Matteson, Eric L; Dejaco, Christian; Dasgupta, Bhaskar
Abstract: Glucocorticoids are the mainstay of treatment for GCA. Patients often require long-term treatment that may be associated with numerous adverse effects, depending on the dose and the duration of treatment. Trends in recent decades for glucocorticoid use in GCA suggest increasing cumulative doses and longer exposures. Common adverse events (AEs) reported in glucocorticoid-treated GCA patients include osteoporosis, hypercholesterolaemia, hypertension, posterior subcapsular cataract, infections, diabetes mellitus, Cushingoid appearance, adrenal insufficiency and aseptic necrosis of bone. AEs considered most worrisome by patients and rheumatologists include weight gain, psychological effects, osteoporosis, cardiometabolic complications and infections. The challenge is to maximize the benefit–risk ratio by giving the maximum glucocorticoid treatment necessary to control GCA initially and then to prevent relapse but to give the minimum treatment possible to avoid glucocorticoid-related AEs. We discuss the safety issues associated with long-term glucocorticoid use in patients with GCA and strategies for preventing glucocorticoid-related morbidity.